2018
DOI: 10.1200/jop.17.00040
|View full text |Cite
|
Sign up to set email alerts
|

Cost Differences Associated With Oncology Care Delivered in a Community Setting Versus a Hospital Setting: A Matched-Claims Analysis of Patients With Breast, Colorectal, and Lung Cancers

Abstract: QUESTIONS ASKED: Are there financial ramifications associated with the paradigm shift of cancer care delivery away from community-based clinics (CCs) and toward hospital-based oncology clinics (HCs)? Furthermore, are any cost differences also accompanied by care quality differentials as measured by hospitalizations or emergency department (ED) visits?ReCAPs (Research Contributions Abbreviated for Print) provide a structured, one-page summary of each paper highlighting the main findings and significance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Previous research has shown that, compared with HOPDs, a smaller proportion of patients receiving chemotherapy in MDOs had an emergency department visit within 72 hours of drug therapy administration, while also having substantially lower per-patient costs. 11 Our findings build on that work by providing a comprehensive measure of quality of care-one that measures the quality of cancer drug treatments. Furthermore, we that the higher cost for patients treated at HOPDs was a feature of patients with commercial insurance, but not those with Medicare Advantage, who face similar costs regardless of where they get their treatment.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Previous research has shown that, compared with HOPDs, a smaller proportion of patients receiving chemotherapy in MDOs had an emergency department visit within 72 hours of drug therapy administration, while also having substantially lower per-patient costs. 11 Our findings build on that work by providing a comprehensive measure of quality of care-one that measures the quality of cancer drug treatments. Furthermore, we that the higher cost for patients treated at HOPDs was a feature of patients with commercial insurance, but not those with Medicare Advantage, who face similar costs regardless of where they get their treatment.…”
Section: Discussionmentioning
confidence: 62%
“…10 It is well established that cancer care is costlier per patient in HOPDs than in MDOs. [10][11][12] However, little is known about whether the quality of that care differs between the treatment sites.…”
Section: Introductionmentioning
confidence: 99%
“…Rischin et al used direct and indirect costs based on services received and found that the average chemotherapy treatment was $83 more expensive to deliver in the community than in hospital (Rischin et al, 2000). Gordan et al discovered a significant decrease in cost per patient per month when delivering care in community oncology clinics compared to hospital clinics, primarily driven by the increased cost of chemotherapy and provider visits in hospital-based clinics (Gordan et al, 2018). No previous study of this kind has used the precise, micro-costing method of cost collection used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Initiatives in USA (Lowenthal et al, 1996), Australia (Rischin et al, 2000) and in the United Kingdom (Hall and Lloyd, 2008) have shown success, in terms of patient preference, quality of care and cost, in moving oncology care services from secondary to a primary care setting. A recent study in USA has shown a decreased patient expense for those receiving oncology care in primary care rather than in secondary care setting (Gordan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, a matched-claims analysis of patients with breast, colorectal, and lung cancers found an increased cost of care in patients treated at hospital-based clinics versus community-based clinics. 56 Therefore, our findings may be influenced by the available databases in the community versus academic settings. Furthermore, many recommendations require assessment of individual patient's clinical context and status, patient expenses, third-party payer compensation, and billing data for different providers.…”
Section: The Path Forwardmentioning
confidence: 98%